Studi Literatur: Analisis Kemampuan Berfikir Komputasi Menggunakan Software Matematika Photomath Tingkat SMA - Nur Aisyah; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Developing computational thinking skills in the modern era of mathematics education is becoming increasingly important. Mathematical software such as Photomath offers exciting potential in supporting the development of these capabilities. This article presents an in-depth analysis of the role of Photomath in developing students' computational thinking skills through a literature review study. By identifying and evaluating relevant literature, this article explains Photomath's contribution to the understanding of mathematical concepts and problem-solving processes. The results of the analysis provide valuable insight into the impact of using Photomath on mathematics learning and the development of students' computational thinking skills.